PENGARUH PENDIDIKAN, PELATIHAN (DIKLAT) DAN PENDAMPINGAN TERHADAP MOTIVASI USAHA UMKM PADA PLUT KUMKM PROVINSI NUSA TENGGARA BARAT - Topan Siswanto; Satriawan Satriawan (Fakultas Ekonomi Universitas Islam Al-Azhar, 2021)
ABSTRACT This study aims to determine the significance of education, training and mentoring on the business motivation of MSMEs at PLUT KUMKM, West Nusa Tenggara Province. In this study, using a quantitative research approach, the main focus is to find the influence between variables. Determination of respondents in this study using non probability sampling so that the respondents in this study were 81 respondents. The data analysis tool used is multiple linear regression and analysis of determination with data collection used by using the method of spreading questions in the form of questions at intervals of strongly agree to strongly disagree, in other words using a questionnaire. Until the processing results show that among the education, training and mentoring variables the most dominant and influencing business motivation is mentoring, assuming this assistance is a follow-up to the training that has been previously provided.